Employee Commitment, Job Satisfaction and Organizational Performance among Multigenerational Workforce: Bases for Human Resource Development Plan - Juevesa, Roel D.; Castino, John Michael P.; Juevesa, Cristina V. (International Journal of Management Excellence (ISSN: 2292-1648), 2020)
This study determined the relationship of employee commitment, job satisfaction, and organizational performance among multigenerational workforce as a basis for formulating human resource development plan. The descriptive survey and correlational research design was used employing quantitative method. The data were gathered through the survey questionnaire and administered to the one hundred fifty (150) respondents from teaching and non-teaching personnel of the studied private non-sectarian school. The data gathered were analyzed through frequency, percentage, weighted mean and pearson correlation. The findings of the study revealed that Baby Boomers, Generation X, and Generation Y “agreed” that their commitment has positive correlation to organizational performance (Ho1). It was also found that Baby Boomers, Generation X, and Generation Y are “satisfied” with their job which resulted to positive correlation to organizational performance (Ho2). Given the overall results, the study recommends that human resource development plan which is formulated based on the findings of the study should be adopted by the private non-sectarian school in General Santos City.